Penggunaan Instagram Sebagai Transmedia Storytelling Pada Semesta “Nanti Kita Cerita Tentang Hari Ini” - Tiara Pratiwi; Aghnina Wahdini; Alvikha Adrian (MEDIALOG: Jurnal Ilmu Komunikasi, 2020)
The presence of social media brought positive impact on various aspects in socio-economic context. Social media gave people the opportunity to promote their own product or creation in a wide, interconnected network allowing the product to be published on multiple platforms. As one of the most popular social media, Instagram aren’t only used to share pictures and videos, but also to share narrative content as Marchella FP has done. NKCTHI is growing as an intellectual property, but it hasn’t reached a stage where fans are allowed to actively contribute to the universe. Marchella still has absolute control over its creation. So far there isn’t any fan who are willing to contribute an independent creation to NKCTHI universe and yet she released the third book called “Nanti Kita Cerita Tentang Hari Ini” as a response to a demand from the mass audience. This research focuses on how Instagram are used to widen her reach and also to how she used different medium to expand NKCTHI as a universe. This research is based on transmedia storytelling concept, in which stories are told through multiple medium. This research is done using qualitative descriptive approach, and using observation and secondary data as analysis unit